2021
DOI: 10.1097/ta.0000000000003449
|View full text |Cite
|
Sign up to set email alerts
|

New Injury Severity Score and Trauma Injury Severity Score are superior in predicting trauma mortality

Abstract: BACKGROUND:Trauma scores are used to give clinicians appropriate quantitative context in making decisions. Studies show that anatomical trauma scores predicted intensive care unit admission better, while physiological trauma scores predicted mortality better. We hypothesize that trauma scores have a hierarchy of efficacies at predicting mortality and operative decision making. METHODS:We performed a retrospective analysis of our trauma patient database at a level 1 trauma center from 2016 to 2020 and calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…The ISS between the two groups was different ( P = 0.019). The distribution of ISS category [ 18 ] was not significantly different, nor was the surgery selected. However, the time to an emergency operation in the “after trauma centre” group was markedly shorter than that in the “before trauma centre” group ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The ISS between the two groups was different ( P = 0.019). The distribution of ISS category [ 18 ] was not significantly different, nor was the surgery selected. However, the time to an emergency operation in the “after trauma centre” group was markedly shorter than that in the “before trauma centre” group ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Os "filtros de auditoria" ou Filtros de Qualidade (FQ) são variáveis propostas pelos assistentes de cada serviço a serem monitoradas e que, quando presentes, podem representar oportunidades de melhora para o sistema [20][21][22][23][24][25] Além dos dados clínicos-demográficos, foi realizada a coleta de informações dirigida para avaliação de qualidade de atendimento, através de Filtros de Qualidade/ Auditoria, conforme aqueles já estabelecidos em nosso serviço 35,36 , baseados naqueles propostos inicialmente pelo American College of Surgeons em 199026 adaptando-nos o à realidade de nosso serviço e editando-os (Tabela 1). Houve 17 fraturas de ossos do crânio (3,65%), 21 fraturas de face (4,7%), 9 Hematomas Epidurais (2%), 8 Hematomas Subdurais (1,8%) e 12 contusões cerebrais (2,7%); 42 fraturas de membros superiores (9,1%), 50 de membros inferiores (10,8%) -com apenas 1 lesão vascular periférica -15 de pelve (3,2%) e 18 de coluna (3,9%).…”
Section: R E S U M O R E S U M Ounclassified
“…The Injury Severity Score (ISS) and New Injury Severity Score (NISS) are valuable trauma scoring systems in showing trauma severity (9). The NISS is one of the trauma scoring systems that best predict mortality [10]. Li and Ma reported that NISS was more valuable than ISS in predicting mortality in patients with severe blunt trauma [11].…”
Section: Experimental Biomedical Researchmentioning
confidence: 99%